2015
DOI: 10.5267/j.ijiec.2015.3.002
|View full text |Cite
|
Sign up to set email alerts
|

Machining parameter optimization in turning process for sustainable manufacturing

Abstract: There is an increase in awareness about sustainable manufacturing process. Manufacturing industries are backbone of a country's economy. Although it is important but there is a great concern about consumption of resources and waste creation. The primary aim of this study was to explore sustainability concern in turning process in an Indian machining industry. The effect of cutting parameters, Speed/Feed/Depth of Cut, the machining environment, Dry/MQL/Wet, and the type of cutting tool on sustainability factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Although this is not the smallest value of surface roughness, it is still relatively small, ranked tenth out of twenty-seven trials (higher than trial No.1, No. 10,No.11,No.12,No.19,No.20,No.21,No.24 and No.25). It can be said that considering purpose of determining the value of the input parameters for achieving the "minimum" surface roughness and the "maximum" MRR, test No.9 is "the best".…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although this is not the smallest value of surface roughness, it is still relatively small, ranked tenth out of twenty-seven trials (higher than trial No.1, No. 10,No.11,No.12,No.19,No.20,No.21,No.24 and No.25). It can be said that considering purpose of determining the value of the input parameters for achieving the "minimum" surface roughness and the "maximum" MRR, test No.9 is "the best".…”
Section: Resultsmentioning
confidence: 97%
“…Several researchers optimized the AISI 1040 steel turning process [10]. In their study, three cutting tools including Brazed tip, TiN coated insert and TiAlN coated insert were used in three cutting environment including dry, MQL and wet.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment was carried out to optimize the cutting factors while machining AISI 1040 carbon steel with CNMG 12012 TF aluminum tungsten nitride coated insert and CNMG 120412 MP tungsten nitride coated insert for different machining parameters. The results obtained from this study suggested that the machining condition and cutting insert type influenced the power consumption while machining AISI 1040 [5].…”
mentioning
confidence: 82%
“…Minimum quantity lubrication (MQL) technology improves overall machining performance in terms of cutting fluid consumption [ 188 ]. The cutting environment is an important parameter for energy consumption compared to others, as pump power in wet conditions and compressor power in MQL conditions are added for measuring the total energy [ 186 ]. To achieve environmentally friendly manufacturing, dry cutting is highly recommended [ 62 ].…”
Section: Optimization With Cooling/lubrication Techniques For Energy ...mentioning
confidence: 99%